Text Encryption Analysis of Modified Symmetric Keys using Genetic Algorithm on Caesar Cipher and One Time Pad - Kurniasih, Julia; Rezalti, Dian Tiara (Universitas Sebelas Maret, 2022)
The problem of data security is essential because data must be maintained securely and in its integrity, starting with the sending procedure and ending with the intended recipient. One way to maintain data security is to use cryptographic techniques, which use data encryption characteristics to transmit messages in secret (information encoding). Information can be encrypted using the Caesar Cipher and One Time Pad, symmetric key cryptographic algorithms. The key must be changed as a critical component of the cryptographic procedure to enhance the data or text's security. This study aims to analyse text encryption on the Caesar Cipher and One Time Pad (OTP) algorithms using a modified symmetric key by implementing a Genetic Algorithm, an optimisation algorithm. The research phase begins by adjusting the key using two types of Genetic Algorithm crossover operators, one-point crossover and two-point crossover, applied to the Caesar Cipher and OTP algorithms. Then testing and analysis of the ciphertext strength are carried out by comparing the frequency of character repetition with the results of implementing the two modification keys to determine which encoding model provides a better data security strength.